PROFITABILITAS USAHA PETERNAKAN AYAM PEDAGING â€œFKâ€ DI DESA MATUNGKAS KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Sheyren Carmella Effendy; Nordy F.L. Waney; Yolanda P. I. Rori (Sam Ratulangi University, 2017)
This study aims to determine the profitability of broiler farming business owned by FK for 1 year in Matungkas Village Dimembe Subdistrict of North Minahasa Regency based on Profit Margin Ratio on Sales, ROA, ROE. This research is Case Study study using Primary data and Secondary data. Primary data collection is done by direct interviews with business owners and employees including business results and costs. Secondary data is obtained from Matungkas Village Office, Dimembe District Office, Minimum BPS Office, Agriculture Department Kab. Minut. Data were analyzed by descriptive method. Profitability of broiler trading business in analysis by using Profit margin on sales analysis, Return On Asset (ROA), Return On Equity (ROE). The results showed Gross profit margin (GPM), Net profit margin (NPM), Return on assets, Return on equity period II and IV increased due to demand of chicken many in that period in August and December due to the need for religious holidays. Periods I, III and V decreased due to reduced production factor and there was no religious holiday period so high profit was in period II and IV.